TRAINING OF ENGINEERS USING THE PROJECT-ORIENTED TEACHING - Igor V. Kovalev; Yuriy Y. Loginov; Pavel V. Zelenkov (Высшее образование в России)
The article focuses on issue of implementation of the project!and!team education technology in the educational process within the framework of a unique project aimed at developing and creation of a series of student small spacecraft. Innovative learning technology developed at the Siberian State Aerospace University in cooperation with strategic partners - JSC «Information Satellite Systems» named after academician M.F. Reshetnev» and Krasnoyarsk Scientific Center of Siberian Branch of the Russian Academy of Sciences. Starting with the third!year of studying, students take part in all stages of satellite constructing - from the development of project documentation to the control of the apparatus in orbit. The student satellite project is divided into 12 directions. The scientific work of each member of a student team belongs to one of these directions. When passing to the following year of study student becomes tutor for younger students engaged in the same section of work. The project helps to identify the best students who are expected to become the most competent and responsible professionals.